Electronic prescription: frequency and severity of medication errors - Rosa,Mário Borges (2019)
SUMMARY OBJECTIVE: To assess the frequency and severity of prescriptions errors with potentially dangerous drugs (heparin and potassium chloride for injection concentrate) before and after the introduction of a computerized provider order entry (CPOE) system. METHODS: This is a retrospective study that compared errors in manual/pre-typed prescriptions in 2007 (Stage 1) with CPOE prescriptions in 2014 (Stage 2) (Total = 1,028 prescriptions), in two high-complexity hospitals of Belo Horizonte, Brasil. RESULTS: An increase of 25% in the frequency of errors in Hospital 1 was observed after the intervention (p<0.001). In contrast, a decreased error frequency of 85% was observed in Hospital 2 (p<0.001). Regarding potassium chloride, the error rate remained unchanged in Hospital 1 (p>0.05). In Hospital 2, a significant decrease was recorded in Stage 2 (p<0.001). A reduced error severity with heparin (p<0.001) was noted, while potassium chloride-related prescription severity remain unchanged (p> 0.05). CONCLUSIONS: The frequency and severity of medication errors after the introduction of CPOE was affected differently in the two hospitals, which shows a need for thorough observation when the prescription system is modified. Control of new potential errors introduced and their causes for the adoption of measures to prevent these events must be in place during and after the implementation of this technology.